Tra filosofia politica e diritto naturale: L’esilio nel trattato «Droit des Gens» di Emer de Vattel (1714-1767) (Balthazar, 2025)
In the political context established with the Peace of Westphalia (1648) and characterized by the Seven Years' War (1756-1763), the Swiss jurist and diplomat Emer de Vattel (1714-1767), considered among the founders of modern international law, in his main work entitled Droit des Gens (1758) dedicates some important reflections on the theme of exile. From the perspective represented by natural law and jus gentium, Vattel analyzes the contents, limits and legal assumptions of the concept of exile, highlighting two focal aspects: the citizen’s right to leave his country and the right to live somewhere. Linked to the concepts of citizenship, sovereignty and freedom, exile is conceived as a person's right, rather than a self-condemnation, in which form it is associated with passive resistance. Voluntary or due to a sovereign act, the right of exile translates into the right of asylum with important consequences in terms of relations between States.